Mortality of tuberculosis patients in Chennai, India - C Kolappan; R Subramani; K Karunakaran; PR Narayanan (The World Health Organization, 2006)
OBJECTIVE: We aimed to measure the mortality rate and excess general mortality as well as identify groups at high risk for mortality among a cohort of tuberculosis patients treated in Chennai Corporation clinics in south India. METHODS: In this retrospective cohort study we followed up 2674 patients (1800 males and 874 females) who were registered and treated under the DOTS strategy in Chennai Corporation clinics in 2000. The follow-up period from the date of start of treatment to either the date of interview, or death was 600 days. FINDINGS: The mortality rate among this cohort of tuberculosis patients was 60/1000 person-years. The excess general mortality expressed as standardized mortality ratio (SMR) was 6.1 (95% confidence interval (CI) = 5.4-6.9). Younger patients, men, patients with Category II disease, patients who defaulted on, or failed courses of treatment, and male smokers who were alcoholics, all had higher mortality ratios when compared to the rest of the cohort. CONCLUSION: The excess mortality in this cohort was six times more than that in the general population. Young age, male sex, smear-positivity, treatment default, treatment failure and the combination of smoking and alcoholism were identified as risk factors for tuberculosis mortality. We suggest that mortality rate and excess mortality be routinely used as a monitoring tool for evaluating the efficiency of the national control programme.